Rapid and quantitative detection of Shiga toxin1 and Shiga toxin2 based on multiple targets UPT‐LF assay. Issue 11 (19th July 2020) - Wei, Qiaozhen; Hu, Qiushi; Shi, Fengjuan; Li, Shuang; Sun, Chongsi; Zhang, Huicong; Xue, Lei; Feng, QiuXia; Dong, Jinying; Jiao, Yongjun; Zhou, Lei
Abstract: Shiga toxin‐producing Escherichia coli (STEC) infection causes a series of diseases that are highly pathogenic and deadly in humans and animals, seriously endangering public health. Of the pathogenic factors within STEC, the two groups of Shiga toxin (Stx) consisting Stx1 and Stx2 plays a prominent role in the pathogenesis of STEC infection. In this study, we developed single‐target up‐converting phosphor technology‐based lateral flow assay (Stx‐UPT‐LFA) for the rapid detection of Stx1 and Stx2, respectively, and also developed a dual‐target Stx1/2‐UPT‐LFA based on single‐target strips to detect of Stx1 and Stx2 at the meantime within 20 min. We choose the purified Stx1 and Stx2 standard samples, and the optimum monoclonal antibody (namely 8E7‐E6, 2F6‐F8 for Stx1 and S1D8, S2C4 for Stx2) were selected for use in Stx‐UPT‐LFA in double‐antibody‐sandwich mode. The sensitivities of single‐target Stx‐UPT‐LFA for both Stx1 and Stx2 were 1 ng mL −1 with accurate quantitation ranges of 1–1000 ng mL −1 and 1–800 ng mL −1 respectively. No false‐negative result was found in the Stx2‐UPT‐LFA even with a high‐test concentration up to 1000 ng mL −1 . Meanwhile, both targets detection sensitivities for dual‐target Stx1/2‐UPT‐LFA were 5 ng mL −1, and accurate quantitation ranges were 5–1000 ng mL −1 and 5–800 ng mL −1 for standard Stx1 and Stx2 solutions without cross‐interference between two targets. Both techniques showed good linearities, with a linear fitting coefficient of determination(r) of 0.9058–0.9918. Therefore, the UPT‐LFA could realize simultaneous detection for multiple targets on a single strip and thus to quickly determine the type of infectious Stxs. In addition, the single‐target Stx1‐UPT‐LFA and Stx2‐UPT‐LFA showed excellent specificity to six toxins, even at high concentrations of 1000 ng mL −1 . In conclusion, the developed Stx‐UPT‐LFA allows the rapid, quantitative, reliable and simultaneous detection of Stx1 and Stx2 within 20 min, providing an alternative method for clinical diagnosis of STEC infection.